Pedagogical Support of Foreign Students Social Adaptation in Russian University - Pavlushkina, Tatyana V.; Schepkina, Neile K.; Dvoryankina, Ekaterina K.; Kazinets, Viktor A.; Ledovskikh, Irina A.; Tabachuk, Natalya P.; Shulika, Nadezhda A.; Ashrafullina, Gulnaz S. (International Review of Management and Marketing, 2016)
Social adaptation of foreign students in Russian high schools is a process of active adaptation to the conditions of a new socio-cultural and educational environment. The article is directed on the development of pedagogical support, contributing to the efficiency of this process. The following leading methods for the mentioned problem‘s solving are chosen: modeling, survey, interview, test, ranking, observation, mathematical processing of experimental data. The experiment involves foreign students of the 1st and 2nd courses. The article deals with the specifics of foreign students’ social adaptation in Russian universities, including socio-cultural, socio-psychological, pedagogical aspects; presents the internal and external factors that influence the process of social adaptation of foreign students studying in Russian universities; represents the developed model of pedagogical support of foreign students’ social adaptation in Russian universities, including conceptual, target, process, evaluation-criteria parts; reveals the necessary and sufficient organizational and pedagogical conditions of pedagogical support of foreign students’ social adaptation in Russian universities. Comparison of experimental work results proves the effectiveness of pedagogical support of foreign students’ social adaptation in Russian universities if the necessary and sufficient organizational and pedagogical conditions are created (initiation of foreign students to the traditions and values of the multinational Russian culture, organization of intercultural communication of foreign students with each other and with Russian students; adaptive works organization to form and develop foreign students’ general educational abilities and skills necessary to adapt to the educational process, development of sustained interest and motivation for the future professional activities). Keywords: Social Adaptation, Foreign Students, Pedagogical Support, Russian University. JEL Classifications: A23, I23, I26